Pengaruh Struktur Modal Terhadap Nilai Perusahaan (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Yayu Ramadhanti; Mia Agustina Puspasari (Institut Manajemen Wiyata Indonesia, 2022)
This study aims to analyze the effect of capital structure on firm value. The population of this study are manufacturing companies in the food and beverage sub-sector consumer goods industry listed on the Indonesia Stock Exchange for the period 2012-2016. The research sample was selected using certain criteria, so that 13 companies were selected as the company sample. Data analysis was performed by using multiple linear regression test using SPSS version 20 statistical test tool. The results showed that partially DER had a negative effect on firm value. An increase in DER increases interest expense and lowers profitability. The decline in profitability reduces investors' interest in investing and will have an impact on decreasing stock prices. LDER partially has no effect on firm value. Investors are critical of the use of long-term debt funds, so the ups and downs of the LDER are not always followed by the ups and downs of the PBV.